The Spiritual Experience of Sufi Whirling Dervishes: Rising Above the Separation and Duality of This World. (September 2021) - Harel, Keren; Czamanski-Cohen, Johanna; Turjeman, Nataly
Highlights: Sufi whirling is an Islamic Sufi spiritual ritual of self-pivoting. The Sufi whirling embodied experience has been minimally studied. Sufi whirling may increase body–mind focus, self-regulation, positive affect. Clients expressing through free whirling may benefit from these qualities. Muslim Sufi clients may benefit from integrating Sufi whirling practices in therapy. Abstract: Sufi whirling, which has been minimally studied to date, is an Islamic Sufi spiritual ritual of self-pivoting performed by spiritual seekers known as dervishes. This study empirically evaluates the inner subjective experience of Sufi whirling dervishes (SWDs) to benefit understanding of the experience of clients expressing through free whirling and the cultural competence of dance movement therapists and psychotherapists working with Muslim Sufi clients. The study participants ( N = 44) were adults from the Israeli SWD community. They participated in a Sufi whirling ritual and then wrote their deepest feelings and thoughts to capture their authentic and living experience. Using expressive writing in a hermeneutic phenomenology analytic approach, the "inner experience of the SWD" theme was identified with subthemes of "the Sufi vortex, " "preparations for transitioning, " and "quietness in the center of the vortex." Participants reported that the Sufi vortex drew them into a present, nonjudgmental body–mind state, sweeping them to submit and surrender until they rose above the separation and duality of this world into a unity and wholeness experience. Sufi whirling may increase body–mind focus, self-regulation, positive-affect, unity, and wholeness experience. Clients who express through whirling during therapy may benefit from these qualities.